Study on the phenomenon of Shoaling-Breaking in Water Wave Equation Formulated Using Weighted Total Acceleration Equation - Syawaluddin Hutahean (Institut Teknologi Bandung, 2020)
AbstractThis research is the continuation of previous research conducted by the author, where in this research a wave equation is developed using total acceleration equation for a function f (x, z, t) and formulated using a complete velocity potential. Based on the wave equation, shoaling-breaking model is developed and the breaker height produced by the model is examined. There is a conformity between breaker height a model and breaker height produced by the previous research. AbstrakPenelitian ini merupakan kelanjutan dari penelitian sebelumnya yang dilakukan oleh penulis, dimana pada penelitian tersebut dikembangkan suatu persamaan gelombang dengan mengggunakan total acceleration equation untuk suatu fungsi f (x, z, t) dan dirumuskan dengan menggunakan velocity potential yang lengkap. Berdasarkan persamaan gelombang tersebut dikembangkan model shoaling-breaking dan diteliti breaker height yang dihasilkan model. Diperoleh kesesuaian antara breaker height model yang digunakan dengan breaker height hasil penelitian terdahulu.